2016
DOI: 10.1242/jeb.146837
|View full text |Cite
|
Sign up to set email alerts
|

Previous motor activity affects transition from uncertainty to decision-making in snails

Abstract: One of the most widely accepted benefits of enhanced physical activity is an improvement in the symptoms of depression, including the facilitation of decision making. Up until now, these effects have been shown in rodents and humans only. Little is known about their evolutionary origin or biological basis, and the underlying cellular mechanisms also remain relatively elusive. Here, we demonstrate for the first time that preceding motor activity accelerates decision making in an invertebrate, the pond snail Lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(46 citation statements)
references
References 70 publications
(73 reference statements)
3
41
1
Order By: Relevance
“…Previously, we reported that the behavioral effects of intense locomotion in the Lymnaea stagnalis snail are, in many aspects, similar to those observed in rodents and humans, with a decrease in defensive responses, an increase in general activity (D'yakonova, 2014) and a facilitation of decision-making in the novel environment (Korshunova et al, 2016). Terrestriallike crawling in low water for 2 h prior to the test promoted the transition from slow circular locomotion to the fast goaloriented crawl in asymmetrically lit arena (Korshunova et al, 2016). We concluded that exercise "facilitates the transition from uncertainty to decision-making in snails.…”
Section: Introductionsupporting
confidence: 54%
See 3 more Smart Citations
“…Previously, we reported that the behavioral effects of intense locomotion in the Lymnaea stagnalis snail are, in many aspects, similar to those observed in rodents and humans, with a decrease in defensive responses, an increase in general activity (D'yakonova, 2014) and a facilitation of decision-making in the novel environment (Korshunova et al, 2016). Terrestriallike crawling in low water for 2 h prior to the test promoted the transition from slow circular locomotion to the fast goaloriented crawl in asymmetrically lit arena (Korshunova et al, 2016). We concluded that exercise "facilitates the transition from uncertainty to decision-making in snails.…”
Section: Introductionsupporting
confidence: 54%
“…Enhanced motor activity was evoked (as in Korshunova et al, 2016) by putting the snails into a tank (50 × 50 cm) filled with 1-2 mm layer of water for 2 or 4 h. As was reported earlier this procedure "protected snails from drying but forced them to use intense muscular crawling to compensate for the lack of water supporting the weight of their shells" (Korshunova et al, 2016, Figure 1A). Control snails were kept in deep water so they could use ciliary locomotion in similar light conditions.…”
Section: Forced Locomotion In Low Water (Experiments 1 and 2)mentioning
confidence: 89%
See 2 more Smart Citations
“…Other gastropods, such as T. diomedea and H. crassicornis, use cilia to crawl, and ciliary motor neurons have been identified in both species (Audesirk, 1978;Cain et al, 2006;Crow and Tian, 2003;Popescu and Willows, 1999;Willows et al, 1997). In L. stagnalis, crawling can be ciliary or muscular, resulting in two different speeds of locomotion (Korshunova et al, 2016;Pavlova, 2010), although the two systems may have a common serotonergic innervation (but see Longley and Peterman, 2013). Motor neurons controlling turns have also been studied in some gastropods.…”
Section: Motor Neuronsmentioning
confidence: 99%